Um modelo matemático para estabilidade elástica de cascas cilíndricas enrijecidas - Figueiredo, Cátia Câmara Bandeira de (1988)
A mathematical model to investigate non-linear branching equilibrium paths of stringer stiffened cylindrical shells under axial compression is presented. This model is based on a general displacements solution of the dynamic non-linear differential equilibrium equations for an isotropic thin cylindrical shell. The stiffeners are assumed to be widely spaced discret slender elements and their torsional stiffness are taken into account. The modelling considers, in a consistent way, the coupling between all essential displacements modes - from shell and stiffeners - that occur during the non-linear response of these structures. In other words, this mathematical model allows the elastic stability analysis of stiffened cylindrical panels considering the interaction between local and overall critical (or buckling) modes.